ANALISIS PERILAKU BELANJA ONLINE KONSUMEN SELAMA MASA PANDEMI COVID-19 - NAIMAH, RAHMATUL JANNATIN; Haryanto, Rudy; Urfi, Muhammad Rizqoni (INTEKNA informasi teknik dan niaga, 2021)
This research was conducted to analyze changes in consumer online shopping behavior during the Covid-19 pandemic in the city of Banjarmasin. This study used purposive sampling technique with 100 Banjarmasin City Respondents who had done online shopping activities during the Covid-19 pandemic. The data analysis method used in this research is Central Tendency Analysis. The findings of this study indicate that there were changes in consumer online shopping behavior during the Covid-19 pandemic, including; 1) The intensity of online shopping for the people in the city of Banjarmasin increased during the Covid-19 Pandemic, 2) The increasing amount of money used by consumers to shop online, 3) There are several product categories that are more frequently purchased online, namely fashion and beauty products, food and beverages or snacks, as well as essential kits in the form of masks, sanitizers, disinfectants, face shields, and others.